Penguatan Jejaring Pendidikan Geografi Melalui Penyelenggaraan Lomba Ilmu Bumi Berbasis Kolaborasi Lintas Institusi - Sejati, Sadewa Purba; Sekarsih, Fitria Nuraini; Suherningtyas, Ika Afianita; Arsanti, Vidyana; Riasasi, Widiyana; Permatasari, Afrinia Lisditya; Nucifera, Fitria (Abdimas Mandalika, 2026)
Abstract:  Contemporary geography education demands spatial, logical, and systematic thinking skills. However, competitive spaces for students remain limited. The objective of this activity is to strengthen geography education networks through the collaborative management of the national Earth Science Competition/ Lomba Ilmu Bumi (LAMBUMI). The implementation method uses a collaborative partnership approach between the Geography Study Program of Universitas Amikom Yogyakarta and the Geography Subject Teachers' Forum of Sleman Regency (Musyawarah Guru Mata Pelajaran Geografi (MGMP) Kabupaten Sleman), consisting of pre-activity, a one-day intensive competition (CBT and final oral examination), and evaluation. The results showed high enthusiasm with 150 participants from various schools across the Special Region of Yogyakarta (DIY), Central Java, West Java, and East Java. The competition successfully fostered in-depth discussion between academics and teachers and improved students' agility in solving spatial problems. Although most participants were from DIY, the activity effectively strengthened educational networks and geospatial literacy. The evaluation noted the need for improved time management and assessment transparency for future implementation.Abstrak: Pendidikan geografi kontemporer menuntut kecakapan berpikir spasial, logis, dan sistematik yang melampaui pemahaman tekstual. Namun, ruang kompetisi yang mewadahi kemampuan tersebut bagi siswa masih terbatas. Tujuan kegiatan pengabdian ini adalah memperkuat jejaring pendidikan geografi melalui kolaborasi manajemen kompetisi Lomba Ilmu Bumi (LAMBUMI) tingkat nasional. Metode pelaksanaan menggunakan pendekatan kemitraan kolaboratif antara Prodi Geografi Universitas Amikom Yogyakarta dan MGMP Geografi Kabupaten Sleman, yang meliputi tahap pra-kegiatan, kompetisi intensif satu hari (CBT dan final tanya jawab), serta evaluasi. Hasil kegiatan menunjukkan antusiasme tinggi dengan partisipasi 150 siswa dari berbagai sekolah di DIY, Jawa Tengah, Jawa Barat, dan Jawa Timur. Kompetisi ini berhasil menciptakan ruang diskusi mendalam antara akademisi dan guru serta meningkatkan ketangkasan siswa dalam menyelesaikan persoalan keruangan. Meskipun mayoritas peserta berasal dari DIY, kegiatan ini efektif memperkuat jejaring pendidikan dan literasi geospasial. Evaluasi mencatat perlunya efisiensi manajemen waktu dan transparansi penilaian untuk pelaksanaan mendatang.